2008
DOI: 10.1002/em.20431
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl trisulfide selectively causes Bax‐ and Bak‐mediated apoptosis in human lung cancer cells

Abstract: Garlic-derived organosulfur compounds (OSCs) are highly effective in affording protection against chemically-induced pulmonary carcinogenesis in animal models. We now demonstrate that garlic constituent diallyl trisulfide (DATS) suppresses viability of cultured human lung cancer cell lines H358 (a non-small cell lung cancer cell line) and H460 (a large cell lung cancer cell line) by causing G2-M phase cell cycle arrest and apoptotic cell death. On the other hand, a normal human bronchial epithelial cell line B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 46 publications
4
58
0
Order By: Relevance
“…Indeed, results obtained by Xiao et al indicated that DAS 3 -treated prostate cancer cells exhibited a decrease in Cdc25 C protein level and an increase in its Ser216 phosphorylation, creating a binding site for 14-3-3 cytoplasmic protein (7). More recently, they have reported that the DAS 3 -mediated G 2 -M cell cycle arrest was associated with a down-regulation of Cdc25 C expression (26). The latter study also shows that the induction of proapoptotic proteins and the decrease of anti-apoptotic proteins seem to be crucial in apoptosis induction.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, results obtained by Xiao et al indicated that DAS 3 -treated prostate cancer cells exhibited a decrease in Cdc25 C protein level and an increase in its Ser216 phosphorylation, creating a binding site for 14-3-3 cytoplasmic protein (7). More recently, they have reported that the DAS 3 -mediated G 2 -M cell cycle arrest was associated with a down-regulation of Cdc25 C expression (26). The latter study also shows that the induction of proapoptotic proteins and the decrease of anti-apoptotic proteins seem to be crucial in apoptosis induction.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that diallyl trisulfide is considerably more effective than either diallyl sulfide or diallyl disulfide against lung cancer cells proliferation (Xiao et al 2009), indicating that a subtle change in the structure of these bioactive agents could have a significant impact on its biological activity.…”
Section: Organosulfur Compoundsmentioning
confidence: 98%
“…Diallyl trisulfide, another garlic-derived organosulfur compounds, suppresses viability of human lung cancer cell lines H358 (a non-small cell lung cancer cell line) and H460 (a large cell lung cancer cell line) by causing cell cycle arrest and apoptosis (Xiao et al 2009). It has been shown that diallyl trisulfide is considerably more effective than either diallyl sulfide or diallyl disulfide against lung cancer cells proliferation (Xiao et al 2009), indicating that a subtle change in the structure of these bioactive agents could have a significant impact on its biological activity.…”
Section: Organosulfur Compoundsmentioning
confidence: 99%
“…OSCs activate Bax and Bak (Cerella et al, 2009;Kim, Y.A. et al, 2007;Xiao et al, 2006a;Xiao et al, 2009a). Interestingly, time-course analyses have evidenced that Bak might be activated before Bax (Cerella et al, 2009).…”
Section: Modulation Of Bcl-2 Family Members By Oscsmentioning
confidence: 99%